2006
DOI: 10.1615/jlongtermeffmedimplants.v16.i2.30
|View full text |Cite
|
Sign up to set email alerts
|

Histological Evaluation, in Rabbit Tibiae, of Osseointegration of Mini-implants in Sites Prepared with Er:YAG Laser versus Sites Prepared with Traditional Burs

Abstract: In comparison with the traditional drilling procedures, Er:YAG laser can be considered efficient in surgery of the bone without inducing irreversible damages, even if it is possible to observe the presence of some carbonized amorphous tissue in the early part of the healing process. This tissue is progressively resorbed in a way similar to a bone graft and doesn't impede the bone formation and osseointegration processes. Further clinical and histological studies are necessary to better define this amorphous ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 0 publications
2
18
0
1
Order By: Relevance
“…Thus, it is not possible to affirm that the chemical constitution of the amorphous layer produced by the Er:YAG laser is the same as that produced by the Er,Cr:YSGG laser, especially when one considers the variations in the laser parameters used in the different studies. Nevertheless, the bone formation pattern found in previous studies 15,16,32‐34 and described in the present research demonstrates that the amorphous line persists in late stages of the bone repair process. The results indicate that the presence of the changed layer is not a factor that obstructs bone neoformation; however, its rate of resorption is slow, and neoformation takes place only in areas in which this layer was resorbed previously.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Thus, it is not possible to affirm that the chemical constitution of the amorphous layer produced by the Er:YAG laser is the same as that produced by the Er,Cr:YSGG laser, especially when one considers the variations in the laser parameters used in the different studies. Nevertheless, the bone formation pattern found in previous studies 15,16,32‐34 and described in the present research demonstrates that the amorphous line persists in late stages of the bone repair process. The results indicate that the presence of the changed layer is not a factor that obstructs bone neoformation; however, its rate of resorption is slow, and neoformation takes place only in areas in which this layer was resorbed previously.…”
Section: Discussionsupporting
confidence: 55%
“…An important fact demonstrated by the histologic analyses is the presence of a continuous amorphous basophilic line followed by an area of bone necrosis in the laser group samples. This structure has been presented by previous studies evaluating bone ablation with erbium lasers (Er:YAG and Er,Cr:YSGG lasers), and most researchers suggest that the amorphous basophilic line is the result of bone melting or carbonization 15,25,32‐34 . After osteotomy with the Er:YAG laser in rat skulls, el Montaser et al 34 described the carbonized layer to be constituted by a dense carbon mass and associated with areas of bone necrosis, which persisted after a period of 105 days of repair.…”
Section: Discussionmentioning
confidence: 87%
“…Ishikawa and colleagues 23 reported that the Er:YAG laser possesses characteristics suitable for oral treatment because of its dual ability to ablate soft and hard tissues with minimal damage. 23 In the study of Salina and colleagues, 25 the different bone reactions in rabbit tibiae after the insertion of mini-implants, using two different techniques of site preparation, were evaluated. It was recommended that, in comparison with traditional drilling procedures, the Er:YAG laser can be considered efficient in bone surgery without inducing irreversible damage.…”
Section: Discussionmentioning
confidence: 99%
“…Use of lasers in these procedures may have several advantages, including improved hemostasis, production of a fine cutting surface with less patient discomfort during the postoperative period, and favorable and rapid healing following abutment placement, thus permitting a faster rehabilitative phase (41,42). Furthermore, because of the ability of the laser to produce effective bone tissue ablation, some researchers have suggested using the Er:YAG laser to prepare osteotomies In the bone tissue (osteotomy} in order to achieve faster osseointegration of the placed implants and to produce less tissue damage in comparison to conventional bur drilling (43,44,45,46). Although these studies demonstrated uneventful wound healing of the laserprepared fixture holes and effective osseointegration, the results are still controversial and there was no consensus regarding the superiority of the application of lasers.…”
Section: Implant Therapymentioning
confidence: 99%